Development of a district mental healthcare plan in Uganda. (January 2016) - Kigozi, Fred N.; Kizza, Dorothy; Nakku, Juliet; Ssebunnya, Joshua; Ndyanabangi, Sheila; Nakiganda, Blandina; Lund, Crick; Patel, Vikram
Abstract : Background: Evidence is needed for the integration of mental health into primary care advocated by the national health sector strategic investment plan in Uganda. Aims: To describe the processes of developing a district mental healthcare plan (MHCP) in rural Uganda that facilitates integration of mental health into primary care. Method: Mixed methods using a situational analysis, qualitative studies, theory of change workshops and partial piloting of the plan at two levels informed the MHCP. Results: A MHCP was developed with packages of care to facilitate integration at the organisational, facility and community levels of the district health system, including a specified human resource mix. The partial embedding period supports its practical application. Key barriers to scaling up the plan were identified. Conclusions: A real-world plan for the district was developed with involvement of stakeholders. Pilot testing demonstrated its feasibility and implications for future scaling up.